Co-creative Media in Remote Indigenous Communities - Rennie Ellie (Cultural Science)
This paper examines co-creative video outputs that have originated from, or relate to, remote Indigenous communities in Australia. Scholarly work on remote media has mostly operated at the interface of media studies and anthropology, seeking to identify how cultural systems shape the production, distribution and reception of media in Aboriginal communities. This paper looks instead at content themes, funding sources and institutions during the 2010-2013 period, and examines the factors that may be determining the quantity of co-creative outputs, as well as the types of stories that get produced. I argue that the focus on culture has obscured important shifts in remote media policy and funding, including a trend towards content designed to address social disadvantage.